Coaches as boundary spanners? Conceptualising the role of the coach in sport and social policy programmes. Issue 3 (3rd July 2019) - Jeanes, Ruth; Rossi, Tony; Magee, Jonathan; Lucas, Ryan
ABSTRACT: Sport has become an important component of programmes seeking to address major challenges or 'wicked problems' within the UK, particularly those affecting young people. This article draws on a single case study analysis to examine the role of a coach within a sport and social policy programme. It draws on the policy concept of 'boundary spanners' to conceptualise and highlight the important work the coach undertook in connecting different agencies to provide a support system for young people taking part in the programme. In doing this, the coach's role moved beyond face-to-face engagement with participants and instead saw him positioned as a critical actor who supported multi-sectoral working. Drawing on concepts identified within boundary spanning literature, the article identifies the key skills the case study coach required to perform this role and discusses the value of considering coaches as boundary spanners more broadly. The article concludes by discussing some of the implications of conceptualising coaching in this way. These include acknowledging the importance of the coach in achieving social policy objectives, re-conceptualising what is 'good' coaching in this setting and the need for coaches working in social policy contexts to have access to education that moves beyond sport-specific knowledge.